2019
DOI: 10.3324/haematol.2019.224501
|View full text |Cite
|
Sign up to set email alerts
|

Tuning mTORC1 activity dictates the response of acute myeloid leukemia to LSD1 inhibition

Abstract: Lysine specific demethylase-1 (LSD1) has been shown to be critical in acute myeloid leukemia (AML) pathogenesis and this has led to the development of LSD1 inhibitors (LSD1i) which are currently tested in clinical trials. Nonetheless, preclinical studies reported that AML cells frequently exhibit intrinsic resistance to LSD1 inhibition, and the molecular basis for this phenomenon is largely unknown. We explored the potential involvement of mammalian target of rapamycin (mTOR) in mediating the resistance of leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…This hypothesis is supported by the evidence that various miRNAs can modulate GSE1 expression 31,32,46 . Alternatively, GSE1 downregulation could be caused by the block of its translational initiation 47 , in line with recent data showing that -in some cell lines-LSD1 inhibitors activate the mTOR signalling cascade 48,49 , which directly affects protein synthesis 50 .…”
Section: Discussionsupporting
confidence: 67%
“…This hypothesis is supported by the evidence that various miRNAs can modulate GSE1 expression 31,32,46 . Alternatively, GSE1 downregulation could be caused by the block of its translational initiation 47 , in line with recent data showing that -in some cell lines-LSD1 inhibitors activate the mTOR signalling cascade 48,49 , which directly affects protein synthesis 50 .…”
Section: Discussionsupporting
confidence: 67%
“…Cancer immunotherapy is one of the new approaches that is currently studied in an attempt to uncover new opportunities for better outcomes for cancer patients [1] , [2] . It is a newly added pillar of oncotherapy in addition to the conventional therapies, i.e., chemotherapy, surgery, and radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…2D). In a follow-up experiment, LSD1i primed P31/Fuj cells to the effects of MEKi ( 34 , 35 )—that is, suppression of proliferation and induction of apoptosis—in a dose-dependent manner (Fig. 2E).…”
Section: Resultsmentioning
confidence: 96%
“…Thus, MEKi and LSD1i are unlikely to be of significant clinical utility as single agents in unselected AML patient populations. Targeting of LSD1 in conjunction with mTOR inhibitors has been shown to induce apoptosis and reduce viability of AML cells ( 34 , 35 ). Crucially, however, LSD1 and mTOR inhibitors were tested as a cotreatment in these studies, and the cells found to be susceptible are limited to specific subgroups of MLL AML.…”
Section: Discussionmentioning
confidence: 99%